The distinctive geographic patterns of common pigmentation variants at the OCA2 gene - Kidd, Kenneth K.; Pakstis, Andrew J.; Donnelly, Michael P.; Bulbul, Ozlem; Cherni, Lotfi; Gurkan, Cemal; Speed, William C. (Nature Portfolio, 2020)
Oculocutaneous Albinism type 2 (OCA2) is a gene of great interest because of genetic variation affecting normal pigmentation variation in humans. The diverse geographic patterns for variant frequencies at OCA2 have been evident but have not been systematically investigated, especially outside of Europe. Here we examine population genetic variation in and near the OCA2 gene from a worldwide perspective. The very different patterns of genetic variation found across world regions suggest strong selection effects may have been at work over time. For example, analyses involving the variants that affect pigmentation of the iris argue that the derived allele of the rs1800407 single nucleotide polymorphism, which produces a hypomorphic protein, may have contributed to the previously demonstrated positive selection in Europe for the enhancer variant responsible for light eye color. More study is needed on the relationships of the genetic variation at OCA2 to variation in pigmentation in areas beyond Europe.
Keywords: Eye-Color; P-Gene; Hair Color; Haplotype; Panel; Snps; Oca2-Asterisk-481Thr; Hypopigmentation; Polymorphisms; Association